Hemolytic staining of the endocardium of the left heart chambers: a new sign for autopsy diagnosis of freshwater drowning - Zátopková, Lenka; Hejna, Petr; Janík, Martin (Forensic science, medicine, and pathology, 2015)
Despite the availability of modern imaging and molecular tools, traditional autopsy, and laboratory findings remain the gold standard for the diagnosis of drowning. This article presents two cases of freshwater drowning in which hemolytic staining of the endocardium of the left heart chambers was observed at autopsy. One case was a suicidal drowning of an 84-year-old man, and the other case was an accidental drowning of an 86-year-old woman. In both cases, there was marked hemolytic staining of the endocardium of the left atrium and ventricle. The endocardium of the right heart chambers was clear and transparent in appearance. Hemolytic intimal staining of the aortic root was observed in one case. Gettler's test was positive in both cases. Hemolytic discoloration of the endocardium of the left heart chambers after freshwater drowning is analogous to hemolytic staining of the aortic root. Both staining patterns result from the hypo-osmolar hemolysis that occurs in the left heart chambers and systemic circulation after hypotonic fluid passes across the alveolocapillary membrane. Hemolytic discoloration of the endocardium of the left heart chambers at autopsy may support a diagnosis of freshwater drowning.
Keywords: Heart Ventricles; senioři nad 80 let; Predictive Value of Tests; Humans; sladká voda; Heart Atria; Endocardium; Aged, 80 and over; Autopsy; Fatal Outcome; Suicide; Forensic Pathology; fatální výsledek; mužské pohlaví; příčina smrti; Hemolysis; hemolýza; úrazy a nehody; utonutí; sebevražda; Accidents; endokard; Drowning; srdeční síně; ženské pohlaví; soudní patologie; pitva; lidé; srdeční komory; prediktivní hodnota testů; Male; Cause of Death; Fresh Water; Female